2021
DOI: 10.3390/metabo11100688
|View full text |Cite
|
Sign up to set email alerts
|

The Interface amongst Conserved and Specialized Pathways in Non-Paclitaxel and Paclitaxel Accumulating Taxus Cultures

Abstract: Plant cell cultures derived from Taxus are used to produce valuable metabolites like paclitaxel, a chemotherapeutic drug. Methyl jasmonate elicitation enhances paclitaxel accumulation, but also inhibits culture growth and increases phenylpropanoid biosynthesis, two side effects that detract from taxane accumulation. To understand the connection between all of these processes, a systems approach is applied to investigate cell-wide metabolism in Taxus. Non-paclitaxel and paclitaxel accumulating cultures were eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…These results are in agreement with literature findings. For example, McKee et al [19] reported that MeJ treatment of T. cuspidata cell cultures only led to increasing in paclitaxel content if this compound was present in the culture before the elicitation. If paclitaxel was initially absent in the cell culture, MeJ could not induce its synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with literature findings. For example, McKee et al [19] reported that MeJ treatment of T. cuspidata cell cultures only led to increasing in paclitaxel content if this compound was present in the culture before the elicitation. If paclitaxel was initially absent in the cell culture, MeJ could not induce its synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…MeJ has been used for elicitation of yew cell cultures since 1990s [15,16,4]. However, there are evidences that MeJ effect may be species-and even genotype-specific and vary depending on culture conditions, possibly due to a cross-talk between MeJ and other growth regulators in culture medium [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al found that MeJA promoted the release of volatile substances in Styrax japonicus [ 21 ]. In a newly published study on paclitaxel biosynthesis, MeJA was found to induce the accumulation of paclitaxel in taxus cultures [ 22 ]. Transcription factors play an important role in the regulation of plant metabolism by MeJA, and are an indispensable member of plant growth and development, stress response and metabolite biosynthesis [ 23 , 24 , 25 , 26 ], such as the transcription factor MYC4 positively regulates MeJA-induced terpenoid synthesis in lavender [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthetic pathway for synthesis of paclitaxel is highly complex—it is a cyclic diterpenoid that is synthesized from the terpene precursors IPP and DMAPP via a branching pathway that includes 19 putative enzymatic steps, 15 of which have been characterized ( Sanchez-Muñoz et al, 2020 ). While much effort has been devoted to studying paclitaxel biosynthesis, comparatively little work has been done to understand how paclitaxel biosynthesis interacts with other secondary metabolic pathways that may compete for cellular resources ( McKee et al, 2021 ). Thus, to improve yields of paclitaxel from PCC, it is vital to understand and manipulate not only paclitaxel biosynthesis, but also the many other metabolic pathways that make up primary and secondary metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel biosynthesis is hypothesized to interact with phenylpropanoid biosynthesis, as both pathways utilize the aromatic amino acid phenylalanine as a common precursor ( McKee et al, 2021 ). In paclitaxel biosynthesis, α-phenylalanine is converted to β-phenylalanine via the enzyme phenylalanine aminomutase (PAM), which is then ligated to acetyl-CoA and attached to the taxane backbone via the enzyme BAPT ( Sanchez-Muñoz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%